2014
DOI: 10.15832/tbd.19830
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Different Harvest Stages on Chemical Composition and Antioxidant Capacity of Essential Oil from Artemisia annua L.

Abstract: Chemical composition of the essential oils obtained by hydro-distillation from Artemisia annua L. (Asteraceae) harvested before flowering (BF), 50% of flowering (50%F), full flowering (FF), and after flowering (AF) stages were determined using GC and GC/MS analysis. The essential oil contents were 0.8%, 0.96%, 1.22% and 1.38% in BF, 50% F, FF and AF, respectively. In total, 20 compounds were identified, with artemisia ketone (28.30%-37.15%), camphor (18.00%-23.30%), and 1,8-cineole (9.00%-10.39%) as main compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…It is shown that the different harvest stages had a significant effect on the percentage, chemical composition, and antioxidant capacity of the essential oil from A. annua . While the essential oil was found to be low in the CD stage (0.80%), it increased in the later harvest stages (0.96%, 1.22 and 1.38% for the 50% W, LO, and LW stages, respectively) 38 …”
Section: Resultsmentioning
confidence: 86%
“…It is shown that the different harvest stages had a significant effect on the percentage, chemical composition, and antioxidant capacity of the essential oil from A. annua . While the essential oil was found to be low in the CD stage (0.80%), it increased in the later harvest stages (0.96%, 1.22 and 1.38% for the 50% W, LO, and LW stages, respectively) 38 …”
Section: Resultsmentioning
confidence: 86%
“…Essential oil of sweet wormwood from Zagreb locality contained high levels of artemisia ketone (46.0 %), camphor (18.7 %) and β ‐selinene (8.8 %), while essential oil from Velebit contains camphor (31.5 %) and β ‐selinene (24.6 %) [39] . Sweet wormwood essential oils collected in Italy, [21,40] Serbia, [9,43] Turkey [25] and Iran [45] contain artemisia ketone as the most dominant compound. Sweet wormwood essential oil collected in Tuscany contained artemisia ketone (24.0 %), camphor (17.7 %) and 1,8‐cineole (16.1 %) as the main compounds [21] …”
Section: Resultsmentioning
confidence: 99%
“…Sweet wormwood is a commercial source of essential oil (up to 2 %, w/w) [9] used for flavoring spirits such as vermouth, against foodborne pathogens in food industry, as a supplement in poultry feed, natural insecticide, as well as in production of perfumes and cosmetics [20–25] . Hydrosols or hydrolates (distillate water that remains in Florentine flask with essential oil after essential oil distillation process) are a by‐product of industrial production of essential oils.…”
Section: Introductionmentioning
confidence: 99%
“…When young annual stems are harvested in spring, this process eradicates flower development. At the same time, in many aromatic and medicinal plants, the best essential oils are accumulated at the stages of flower buds and full flowering [ 15 , 16 ]. Therefore, metabolite profiling of the chemical composition and oil content at different developmental stages is critical for the optimization of the harvest period for the desirable products.…”
Section: Introductionmentioning
confidence: 99%